Eskatologi: Perspektif Agama dan Filsafat - Amsal Bakhtiar (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
This passage presents arguments for the existence of an afterlife grounded in rational reasoning and supported by sacred scriptures, aiming to strengthen the faith of religious believers. However, it acknowledges that these arguments may not satisfy adherents of agnosticism and atheism, who often counter them with various reasons. Nevertheless, for the consideration of atheists, the hypothetical scenario is proposed: if there were no Day of Judgment, both religious adherents and atheists would be equally safe, with no loss on either side. Conversely, if the Day of Judgment does indeed occur, believers would be saved while atheists would not, altering the outcome significantly in favor of theism.